The Counsellor as Consultant in the Development of the Teacher-Advisor Concept in Guidance - Simons, Hal; Davies, Dawn (Canadian Journal of Counselling and Psychotherapy, 2012)
Students, teachers, counsellors and administrators will soon findthemselves in a school setting which is quite foreign, and in someaspects beyond their wildest imagination. Ever-enlarging school facilities with resulting increased impersonalization due to sheernumbers, physical and financial limitations on the numbers of counsellors being appointed by school boards; increased demands and responsibilities placed upon coun- sellors, all make necessary an original and innovative look at the structural, organizational, and functionalaspects of counselling and the total guidance program in our schools. Since long-recommended counsellor-student ratios in the vicinity of 300:1 are not likely to materialize in the near future, we feel that it is our responsibility as practising counsellors to devise an approach which will best utilize those resources which already exist, so as to provide more than an "adequate" service to our students. We envisage the use of teachers, administrators, and community agencies in an overall guidance program for a particular school. Utilization of this innovation has been coined as the "teacher-advisor concept". The central consideration of this entire proposal is to view student orientation as the primary goal and subject orientation as the secondary goal (i.e. teachers must realize that the student as an individual is more important than "covering the course"). Most students, during their school career, will have concerns which to them are of a major or minor nature. At these times, they want and need someone to whom they can talk on a personal and confidential basis. If a friendly and concerned (or interested) relationship can be developed between each student and one of his teachers (whom we label a "teacher-advisor"), then many of these concerns can be handled without directly involving a counsellor. Any situations that the teacher-advisor feels he cannot comfortably or adequately handle could then be referred to a counsellor. Generally then, the attitude of students in the larger schools toward the process of education can be improved by greater attention and interest by the school staff toward the individual student. The "teacher-advisor" concept is one method by which this impersonalization can be minimized. Those classroom teachers and administrators who participate, can each be selected (or chosen) by a small number of students (approximately 20). Counsellors can therefore be freed from many routine and time-consuming guidance activities (most of which are important) so as to be available for crisis situations, referrals of a more serious nature from teachers, coordination of community resources, and the increasingly important role of providing in-service and consultative services for the teaching staff.